The Efficacy of Local Flaps in the Treatment of Traumatic Scalp Defects - Stepniewski, Adam; Lehmann, Wolfgang; Schilderoth, Maximilian; Behringer, Dominik; Emmerich, Nadine; Daugardt, Julian; von der Brelie, Christian; Kauffmann, Philipp; Felmerer, Gunther (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Scalp defects represent a therapeutic challenge. The aim of this study is to present our experience with local and regional flaps in the treatment of trauma-induced scalp defects. Furthermore, a comparison with other surgical techniques was performed.Methods A retrospective evaluation of patient records was performed. Only patients who underwent surgery using local flaps between January 2010 and September 2020 due to traumatic scalp defects were included in the study.Results In all, 10 cases were identified (3 females, 7 males, average age at surgery of 46.5 years [range: 18–82 years]). Six patients underwent surgery due to tissue defects and four due to scar keloids. Three patients experienced minor postoperative complications, one of which required additional surgery. The mean defect size was 35.75 cm2 (range: 4–79 cm2) among the four patients where the defect size could be determined retrospectively. The mean inpatient follow-up was 12.4 days (range: 2–34 days).Conclusions Local flaps can be widely used. In carefully selected cases, they have the fewest disadvantages of all surgical techniques. In our experience, large angiosomes of the main scalp arteries allow the treatment of defects larger than 30 cm2 with local flaps. Our experience also suggests that the dimensions of flap length to flap width can exceed a ratio of 2:1 in the scalp.
Keywords: traumatic scalp defects; local flaps; defect therapy; galea